Socioeconomic analysis of producers of maize for self-consumption, case of native peoplein the State of Nayarit - Pérez Robles, Karina; Álvarez López, Plácido Salomón (Revista de Geografía Agrícola, 2020)
This article aims to describe the social and economic situation faced by the native population of the state of Nayarit in relation to the production of maize for self-consumption. The research focused on maize production as an essential element for access to food and reduction of food poverty in this population. The results and analyzes are the product of a socioeconomic diagnosis belonging to the project: "Institutional Model for Sustainable Production of the University of Nayarit". This is a mixed study (quantitative - qualitative), with a multidisciplinary approach. The ethnographic method was used, with participatory planning tools, with analysis of latent structures and analysis of the social discourses of the participating actors in the study communities, under an evaluative research design. It was concluded that maize has been an active element in the social production of native peoples because it represents the ways of relating between settlers and communities, as well as the method of internal organization for production, resource management, family activities and of each native people.